Population genomics of Brazilian native fruit species of Eugenia spp. (Myrtaceae) for conservation and improvement - Sampaio, Laecio Fernandes Souza; Zucchi, Maria Imaculada; Colombo, Carlos Augusto; Jacomino, Angelo Pedro; Figueira, Antonio; Mourão Filho, Francisco de Assis Alves (Frontiers in Plant Science, 2026)
Brazil is a global biodiversity hotspot, especially in the Atlantic Forest biome, which contains a high diversity of native fruit species that remain underutilized and understudied. Native fruit trees, particularly those in the Myrtaceae family, have great potential to become new fruit crops contributing to food security. The genus Eugenia encompasses several native species that have been little investigated, including Eugenia brasiliensis Lam. (grumixama), E. pyriformis Cambess (uvaia), and E. involucrata DC (Rio Grande cherry). This study investigated the genomic diversity and structure of several populations of these three native fruit species using single-nucleotide polymorphism (SNPs) markers obtained through genotyping by sequencing. We analyzed 73 accessions of E. brasiliensis, 93 of E. pyriformis, and 62 of E. involucrata, derived from three, four, and seven populations, respectively, maintained as living collections (due to their desiccation-sensitive seeds) in research institutions, urban afforestation projects, and small rural properties in the states of São Paulo and Minas Gerais, Brazil. The comparison among E. brasiliensis, E. pyriformis, and E. involucrata accessions revealed 2,299, 2,872, and 1,471 SNPs, respectively. These markers effectively characterized each species’ genomic diversity and population structure, revealing levels of diversity (He = 0.22, 0.19, 0.21 for grumixama, uvaia, and Rio Grande cherry respectively) and inbreeding (f = -0.06; 0.05; -0.04, respectively) consistent with their respective mating biology. Significant genetic structure was detected between collections (PhiST = 0.29; 0.10; 0.23 for E. brasiliensis, E. pyriformis, and E. involucrata, respectively), confirmed by discriminant and principal component analyses, indicating an important diversity between and within the collections. The data will serve to identify the most divergent accessions to help prioritize accessions for fruit quality assessments and for conservation, while identifying parents to guide hybridizations to initiate a breeding program. The study highlights the importance of employing population genomics approaches to develop improved management practices for these fruit species, ultimately promoting the conservation and valorization of Brazilian native genetic resources.